(untitled) (The Pakistan Development Review, 1992)
The labour absorptive capacity of the economy is not keeping pace with labour supplies. An almost stagnant annual demand, estimated on the basis of the last few labour force surveys as ranging between 700,000 to 800,000 annually, is now being left far behind by a labour force whose stock is being added by over a million annually.l This phenomenon is building up pressure on the domestic labour market.2 This situation, however, does not seem to be fully explained by the arguments of: (i) a net-return flow in overseas migration, (ii) saturation in the public sector employment, (iii) increasing capital intensity in the organised manufacturing sector, especially in its large-scale units, and (iv) worsening landman ratio in Pakistan’s agriculture. Most of them, in fact, are the outcome of the absence of sufficient and meaningful considerations on employment and manpower development in the whole process of development planning and setting sectoral priorities. Otherwise emergence of this negative situation, to a large extent, could have been avoided. Fortunately, the problem of under-utilisation of manpower, though continuously on the rise, has not assumed such proportions as could not be addressed by appropriate policy interventions. But a further delay in evolving concrete remedial measures, certainly, can lead to the point of no return. This then would be counter-productive and disruptive socio-economically. The author, in this paper, attempts to indicate the existence of possibilities of generating gainful employment opportunities in some sectors/sub-sectors and regions of the economy as well as for certain target groups.